Unemployment, Marginal Attachment and Labor Force Participation in Canada and the United States - Stephen R. G. Jones; W. Craig Riddell (Institute of Labor Economics (IZA), 2017)
We analyze changes in unemployment, marginal labor force attachment and participation in Canada and the U.S.. Using two complementary decompositions, we show the importance for the comparative evolution of aggregate unemployment of changes in the fraction of the non-employed who are unemployed and in the fraction of the unemployed who 'want work'. Using microdata we study labor market transition behavior at these margins, finding remarkably consistent results in the two countries, with the marginally attached displaying behavior lying between unemployment and non-attachment. The three non-employment states are distinct from one another in both Canada and the U.S.
Keywords: E24; E32; J63; J64; 330; unemployment; labor force participation; non-employment; marginal attachment; labor force transitions; heterogeneity